Ca2+‐Dependent Hyperpolarization Pathways in Sleep Homeostasis and Mental Disorders. (4th December 2017) - Shi, Shoi; Ueda, Hiroki R.
Abstract : Although we are beginning to understand the neuronal and biochemical nature of sleep regulation, questions remain about how sleep is homeostatically regulated. Beyond its importance in basic physiology, understanding sleep may also shed light on psychiatric and neurodevelopmental disorders. Recent genetic studies in mammals revealed several non‐secretory proteins that determine sleep duration. Interestingly, genes identified in these studies are closely related to psychiatric and neurodevelopmental disorders, suggesting that the sleep‐wake cycle shares some common mechanisms with these disorders. Here we review recent sleep studies, including reverse and forward genetic studies, from the perspectives of sleep duration and homeostasis. We then introduce a recent hypothesis for mammalian sleep in which the fast and slow Ca 2+ ‐dependent hyperpolarization pathways are pivotal in generating the SWS firing pattern and regulating sleep homeostasis, respectively. Finally, we propose that these intracellular pathways are potential therapeutic targets for achieving depolarization/hyperpolarization (D/H) balance in psychiatric and neurodevelopmental disorders. Abstract : How animals implement sleep homeostasis is a great mystery. Here, we review recent studies with highlighting the hypothesis that the slow Ca 2+ ‐dependent hyperpolarization pathway regulates sleep homeostasis via modifying the fast pathway; the activity of CaMKIIα/β increases during wakefulness, which triggers sleep by phosphorylating the components in the fast pathway.